Thermal Selection Shifts Genetic Diversity and Performance in Blue Mussel Juveniles - Jennifer C. Nascimento‐Schulze; Jahangir Vajedsamiei; Tim P. Bean; Lisa Frankholz; Reid S. Brennan; Frank Melzner; Robert P. Ellis (Evolutionary Applications)
ABSTRACT Exploring evolutionary and physiological responses to environmental stress is crucial for assessing the effects of climate change on wild populations. Mussels, key inhabitants of the benthos with high ecological and economic value, are a particularly vulnerable species that may be pushed to their ecological limits as warming threatens their survival and population stability. Species within the Mytilus edulis complex are commonly found in temperate regions globally; in the Baltic Sea, populations are formed by M. edulis and M. trossulus hybrids with low levels of M. galloprovincialis introgression. This study investigates the mechanisms through which resilience towards global warming may be fast‐tracked in Baltic mussels (Kiel, Germany). For this, we studied two cohorts of juvenile mussels (recently settled animals), one exposed to an extreme heat event early in life and one naïve to this stressor. Both cohorts were later exposed to experimental temperatures ranging from 21°C to 26°C, with animal performance measured after 25 days. Impacts of thermal stress on the genetic composition of each cohort was then assessed by genotyping 50 individuals using a blue mussel 60 K SNP‐array. We observed a significant increase in M. edulis genotypes together with a decrease in M. trossulus in the challenged cohort, compared to naive juveniles. We also found exposure to high temperature affected performance of mussel cohorts, reducing dry tissue weight of selected individuals. Results from this study provide insights on how selection through thermal stress impacts performance and genetic composition of key globally distributed intertidal species, with important implications for understanding and managing mussel populations under future warming scenarios.